Exploration of the temperature-dependent correlations present in the structural, morphological and electrical properties of thermally reduced free-standing graphene oxide papers - Ramamoorthy, Harihara; Buapan, Kanokwan; Chiawchan, Tinna; Thamkrongart, Krongtham; Somphonsane, Ratchanok (Journal of materials science, 2021)
We report on a corroborative study of the structural, morphological and electrical property alterations of free-standing graphene oxide (GO) papers subject to thermal reduction. Structural analysis performed using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Raman techniques prove that the onset of major structural changes, characterized by removal of oxygen functionalities, occur in the 200–300 °C temperature range. The results are corroborated with related morphological changes observed using Scanning electron microscopy (SEM) and Atomic force microscopy (AFM) imaging. Elemental analysis shows the GO paper reduced at 600 °C to contain an 85 wt. % carbon content and a remnant oxygen level of 13.31 wt. %. At the highest reduction temperatures, we see evidence of vacancy-type defects impeding the overall effectiveness of the reduction process. Detailed electrical resistance measurements and current–voltage (I-V) profiling conducted using four-point probe method reveals a several orders of magnitude drop in the sample resistance once the reduction temperature exceeds 200 °C, in good agreement with the structural and morphological changes. The fundamental insights revealed through these studies will be important for future applications where the electrical and mechanical properties of free-standing GO and reduced graphene oxide (rGO) are exploited in practical devices. Graphical abstract